Cartoon classics - Mill Creek Entertainment ([Place of publication not identified] : Mill Creek Entertainment, 2007)
DISC 1: Time for Love, The Little Stranger, Hawaiian Birds, Peeping Penguins, A Car-Tune Portrait, Play Safe, All's Fair at the Fair, Ants in the Plants, The Cobb Web Hotel, Making Friends, Betty in Blunderland, Nearlyweds, Fire Cheese, My Friend the Monkey, On with the New, Pudgy Takes a Bow-Wow, Rhythm on the Reservation, Hairbrained Barbers, Sock-A-Bye Kitty, Comin' Round the Mountain, Crazytown, The Golden State, Winter Draws On, Short'nin' Bread, Once Upon a Time, The Lost Dream, Cad and Caddy, Quack-A-Doodle-Doo, Marriage Wows, Hector's Hectic Life, Be Human, Gabby Goes Fishing, Goofy Goofy Gander, I Don't Scare, The Noisy Silent Movie, The Littlest Martian, Naughty but Nice, Popeye's 20th Anniversary. DISC 2: Alladin and His Wonderful Lamp, Ancient Fistory, Taxi-Turvy, Popeye for President, Assault and Flattery, Fright to the Finish, Bride and Gloom, Gopher Spinach, Customers Wanted, Out to Punch, Popeye Meets Ali Baba's Forty Thieves, Spree Lunch, Greek Mirthology, Parlez Vous Woo, A Haul in One, Insect to Injury, Cookin' with Gags, Floor Flusher, Little Brown Jug, A Date to Skate, Judge for a Day, Is My Palm Read?, Betty Boop's Crazy Inventions, The Friendly Ghost, The Goose that Laid the Golden Egg, Pantry Panic, Spooky Swabs, Snow Foolin', Betty Boop and the Little King, Little Nobody, Get that Snack Shack off the Track, Boo Moon, Patriotic Popeye, Big Bad Sindbad, A Little Soap and Water, The Queen of Hearts.
"Hours of classic animation"--Container
DVD.
112471
Keywords: Animated films; Children's films